EGFR Q787Q Polymorphism Is a Germline Variant and a Prognostic Factor for Lung Cancer Treated With TKIs - Wu, Wen-Jui; Yang, Sheng-Hsiung; Chung, Hsin-Pei; Yen, Chia-Te; Chen, Yen-Ting; Chang, Wei-Chin; Su, Jian; Chen, Hsuan-Yu (Frontiers in Oncology, 2022)
The prevalence and impact of epidermal growth factor receptor (EGFR) Q787Q on the treatment of lung adenocarcinoma remains unclear. We retrospectively analyzed patients with stage IV lung adenocarcinoma to evaluate the prevalence of the EGFR Q787Q mutant and its influence on effects of tyrosine kinase inhibitor (TKI) treatment. A total of 333 patients were included in this study. The prevalence of the EGFR Q787Q polymorphism was 38%, 42%, and 35% in all patients with wild-type EGFR and EGFR mutations, respectively. The prevalence of EGFR Q787Q was significantly higher in EGFR wild-type patients than in the general non-cancerous population from Taiwan Biobank and 1000 Genome Project databases, respectively. EGFR Q787Q had significant protective effects on the overall survival of EGFR-mutant lung adenocarcinoma treated with EGFR TKIs (aHR =0.61, p=0.03). Our study demonstrated that EGFR Q787Q is a germline polymorphism in the general population. It is a protective predictor of overall survival in patients with stage IV EGFR-mutated lung adenocarcinoma treated with TKIs.